In Vivo Ryr2 Editing Corrects Catecholaminergic Polymorphic Ventricular Tachycardia. Issue 8 (28th September 2018) - Pan, Xiaolu; Philippen, Leonne; Lahiri, Satadru K.; Lee, Ciaran; Park, So Hyun; Word, Tarah A.; Li, Na; Jarrett, Kelsey E.; Gupta, Rajat; Reynolds, Julia O.; Lin, Jean; Bao, Gang; et al.
Abstract : Rationale: : Autosomal-dominant mutations in ryanodine receptor type 2 ( RYR2 ) are responsible for ≈60% of all catecholaminergic polymorphic ventricular tachycardia. Dysfunctional RyR2 subunits trigger inappropriate calcium leak from the tetrameric channel resulting in potentially lethal ventricular tachycardia. In vivo CRISPR/Cas9-mediated gene editing is a promising strategy that could be used to eliminate the disease-causing Ryr2 allele and hence rescue catecholaminergic polymorphic ventricular tachycardia. Objective: : To determine if somatic in vivo genome editing using the CRISPR/Cas9 system delivered by adeno-associated viral (AAV) vectors could correct catecholaminergic polymorphic ventricular tachycardia arrhythmias in mice heterozygous for RyR2 mutation R176Q (R176Q/+). Methods and Results: : Guide RNAs were designed to specifically disrupt the R176Q allele in the R176Q/+ mice using the SaCas9 ( Staphylococcus aureus Cas9) genome editing system. AAV serotype 9 was used to deliver Cas9 and guide RNA to neonatal mice by single subcutaneous injection at postnatal day 10. Strikingly, none of the R176Q/+ mice treated with AAV-CRISPR developed arrhythmias, compared with 71% of R176Q/+ mice receiving control AAV serotype 9. Total Ryr2 mRNA and protein levels were significantly reduced in R176Q/+ mice, but not in wild-type littermates. Targeted deep sequencing confirmed successful and highly specific editing of the disease-causing R176Q allele. No detectable off-target mutagenesis was observed in the wild-type Ryr2 allele or the predicted putative off-target site, confirming high specificity for SaCas9 in vivo. In addition, confocal imaging revealed that gene editing normalized the enhanced Ca 2+ spark frequency observed in untreated R176Q/+ mice without affecting systolic Ca 2+ transients. Conclusions: : AAV serotype 9–based delivery of the SaCas9 system can efficiently disrupt a disease-causing allele in cardiomyocytes in vivo. This work highlights the potential of somatic genome editing approaches for the treatment of lethal autosomal-dominant inherited cardiac disorders, such as catecholaminergic polymorphic ventricular tachycardia. Abstract : Supplemental Digital Content is available in the text.